Novel PLEKHG5 mutations in a patient with childhood‐onset lower motor neuron disease. Issue 1 (4th December 2020) - Gonzalez‐Quereda, Lidia; Pagola, Inmaculada; Fuentes Prior, Pablo; Bernal, Sara; Rodriguez, Maria Jose; Torné, Laura; Salgado Garrido, Josefa; Gallano, Pia; Jericó, Ivonne
Abstract: The PLEKHG5 gene encodes a protein that activates the nuclear factor kappa B (NFκB) signaling pathway. Mutations in this gene have been associated with distal spinal muscular atrophy IV and intermediate axonal neuropathy C, both with an autosomal recessive mode of inheritance. Two families with low motor neuron disease (LMND) caused by mutations in PLEKHG5 have been reported to date. We present a third LMND family, the first nonconsanguineous, due to two not previously reported PLEKHG5 mutations. Our results confirm and extend previous findings linking PLEKHG5 mutations to lower motor neuron diseases.